A model of weight‐based stigma in health care and utilization outcomes: Evidence from the learning health systems network. (27th August 2021) - Phelan, Sean M.; Bauer, Katherine W.; Bradley, David; Bradley, Steven M.; Haller, Irina V.; Mundi, Manpreet S.; Finney Rutten, Lila J.; Schroeder, Darrell R.; Fischer, Kristin; Croghan, Ivana
Abstract: Objective: Obesity is stigmatized and people with obesity report experiencing stigmatizing situations when seeking health care. The implications of these experiences are not well understood. This study tests an indirect effects model of negative care experiences as an intermediate variable between obesity and care avoidance/utilization and switching primary care doctors. Methods: A survey was completed by 2380 primary care patients in the Learning Health Systems Network (LHSNet) Clinical Data Research Network with a BMI >25 kg/m 2 . Measures included scales assessing stigmatizing situations, perceived patient‐centered communication, perceived respect, having delayed needed care, and having looked for a new primary doctor in the past 12 months. Sequential and serial indirect effects of care experiences and respect in the association between BMI and care utilization outcomes was modeled. Results: The hypothesized model was supported by findings. The associations between BMI and delaying needed care (OR = 1.06, p  < 0.001) and attempting to switch primary doctors (OR = 1.02, p  = 0.04) was mediated by both stigmatizing situations experienced in a health care context and lower patient‐centered communication. Lower perceived respect mediated the association between care experiences and utilization outcomes. Conclusions: People with higher BMIs may avoid care or switch doctors as a result of stigmatizing experiences and poor communication with doctors. These outcomes may contribute to morbidity in people with obesity if they delay or avoid care for health concerns when symptoms first present.